2008
DOI: 10.1002/cmdc.200800118
|View full text |Cite
|
Sign up to set email alerts
|

Biomedical Potentials of Crown Ethers: Prospective Antitumor Agents

Abstract: Crown ethers are of enormous interest and importance in chemistry, biochemistry, materials science, catalysis, separation, transport and encapsulated processes, as well as in the design and synthesis of various synthetic systems with specific properties, diverse capabilities, and programmable functions. Classical crown ethers are macrocyclic polyethers that contain 3-20 oxygen atoms separated from each other by two or more carbon atoms. They are exceptionally versatile in selectively binding a range of metal i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
69
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(79 citation statements)
references
References 125 publications
(106 reference statements)
1
69
0
1
Order By: Relevance
“…We obtained the same results for the cell viability indicator: about 15% in Down syndrome and more than 60% in cells of healthy donors. Similar results were obtained when using a synthetic product, RUSSIAN [56], whose antimutagenic and anticarcinogenic activity were described in [57]. Consequently, we found that protection of cells in the adaptive response and exposure to antimutagens (retinol, garlic extract, and crown compound) is implemented in different ways, which seems essential to understand the mechanisms of cell protection from damaging impacts.…”
Section: Approach To Reducing the Damaging Effects Of Radiation In Husupporting
confidence: 83%
“…We obtained the same results for the cell viability indicator: about 15% in Down syndrome and more than 60% in cells of healthy donors. Similar results were obtained when using a synthetic product, RUSSIAN [56], whose antimutagenic and anticarcinogenic activity were described in [57]. Consequently, we found that protection of cells in the adaptive response and exposure to antimutagens (retinol, garlic extract, and crown compound) is implemented in different ways, which seems essential to understand the mechanisms of cell protection from damaging impacts.…”
Section: Approach To Reducing the Damaging Effects Of Radiation In Husupporting
confidence: 83%
“…Moreover, the numerous works concerning self-assembled monolayers of macrocyclic complexes with inorganic and organic molecules and ions have been published recently by various research groups worldwide [38][39][40][41]. The numerous crown-containing compounds with various substituents are promissing for application in molecular devices [42], chromatography [43], catalysis [44,45], biomedical fields [46,47], photovoltaics [48,49], hybrids [50,51] and special [52][53][54] materials. …”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, crown ethers have also been shown to have applications in a biological or medicinal context. For example, certain crown ether compounds show high antimicrobial activity . Additionally, crown ethers show potential as anticancer agents and for other biomedical applications .…”
Section: Introductionmentioning
confidence: 99%
“…For example, certain crown ether compounds show high antimicrobial activity . Additionally, crown ethers show potential as anticancer agents and for other biomedical applications . Furthermore, aromatic amino acids bearing crown ether moieties have been synthesized and were successfully used to create artificial ion channels .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation